Structure-Based Approach to the Development of Potent and Selective Inhibitors of Dihydrofolate Reductase from Cryptosporidium - Bolstad, David B. (2008)
Cryptosporidiosis is an emerging infectious disease that can be life-threatening in an immune-compromised individual and causes gastrointestinal distress lasting up to 2 weeks in an immune-competent individual. There are few therapeutics available for effectively treating this disease. We have been exploring dihydrofolate reductase (DHFR) as a potential target in Cryptosporidium. On the basis of the structure of the DHFR enzyme from C. hominis, we have developed a novel scaffold that led to the discovery of potent (38 nM) and efficient inhibitors of this enzyme. Recently, we have advanced these inhibitors to the next stage of development. Using the structures of both the protozoal and human enzymes, we have developed inhibitors with nanomolar potency (1.1 nM) against the pathogenic enzyme and high levels (1273-fold) of selectivity over the human enzyme.